Evaluation of the illuminance on the monitor screen present in the hemodynamics room (Research, Society and Development, 2022)
Objective: To evaluate, using a photometer, the influence of luminance from ambient illuminance reflected on the monitor screen on the visualization of low-contrast structures during hemodynamic procedures. Method: To simulate a low-contrast situation, some PMMA plates were carefully arranged and exposed to radiation, both in normal and low-dose fluoroscopy modes, available in the device. A photometer was used to measure the luminance on the monitor screen and measurements were performed for 12 different lighting scenarios in the hemodynamics room. Results: It was possible to observe from the luminance measurements performed in each scenario, that the positioning of the luminaires can influence the visualization of low-contrast structures on the monitor screen, and that the fact that the luminaires are on or partially off in the hemodynamics room, can be an important factor to ensure the visual comfort of the physician responsible for the procedure.